PERAN ACTIVITY BASED COSTING UNTUK MENETAPKAN HARGA POKOK PRODUK YANG AKURAT - LEVINA SUSANTO (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Determination of accurate product cost is very important for comanies to set prices. This leads to the allocation of overhead cost should be done properly, the company that markets more than one kind of product. Conventional methods that allocate costs based on changes in the costs are not allocated according to the amount of consumsption of each unit. Activity based costing methods by using the allocation of overhead cost based on activities that cause costs seems more appropriate to use. Activity based costing methods led to the allocation of overhead cost is able to bring compliance cost of consumption for each product. Benefits of activity based costing is causing the development of the discussion that aims to provide an understanding of the role of activity based costing to assign an accurate cost of the product.